간호대학생의 MBTI 유형에 따른 셀프리더십, 감성지능, 간호술기 수행자신감이 임상수행능력에 미치는 영향 - 김미혜; 제남주; Mi-Hye Kim; Nam-Joo Je (디지털정책학회지, 2025)
This study was a descriptive research study to identify the impact of self-leadership, emotional intelligence, and confidence in performing nursing skills on clinical performance ability according to MBTI type of nursing students. This study randomly selected nursing students from J-do C university as a proximate population from December 1 to December 15, 2024, and a total of 142 copies were finally analyzed. Descriptive statistics t-test, ANOVA, correlation, and multiple regression analysis were used to analyze the data using IBM SPSS/25. Clinical performance ability was positively correlated with self-leadership, emotional intelligence, and nursing skills performance confidence. Among MBTI, the variables that significantly affected clinical performance ability were the attitude index 'EJ', self-leadership, and nursing skills performance confidence. Nursing skills performance confidence was the factor that best predicted clinical performance ability, followed by self-leadership. The total explanatory power was 59.5%. Based on the results of this study, it is necessary to develop a customized program that reflects MBTI personality types to improve the clinical performance ability of nursing students and examine its effectiveness, thereby improving the self-leadership and confidence in performing nursing skills of nursing students and developing an educational program that enhances clinical performance ability. 본 연구는 간호대학생의 MBTI 유형에 따른 셀프리더십, 감성지능, 간호술기 수행자신감, 임상수행능력 영향요인을 확인하기 위한 서술적 조사연구이다. 본 연구는 J도 C대학교 간호대학생을 근접모집단으로 2024년 12월 01부터 12월 15일까지 임의 표출하였으며, 총 142부를 최종 분석하였다. IBM SPSS/25을 사용하여 기술통계 t-test, ANOVA, 상관관계, 다중회귀분석으로 분석하였다. 임상수행능력은 셀프리더십, 감성지능, 간호술기 수행자신감과 정적 상관관계가 있었다. MBTI 중 임상수행능력에 유의한 영향을 미치는 변인은 태도 지표 'EJ'이며, 셀프리더십, 간호술기 수행자신감이었다. 간호술기 수행자신감이 임상수행능력을 가장 잘 예측하는 요인이며, 그 다음 셀프리더십이었다. 총 설명력은 59.5%이었다. 본 연구결과를 바탕으로 간호대학생들의 임상수행능력 향상을 위한 MBTI 성격유형을 반영한 맞춤형 프로그램을 개발하고 그 효과를 검토함으로써, 간호대학생의 셀프리더십과 간호술기 수행자신감을 향상시키고, 임상수행능력을 높이는 교육 프로그램 개발이 필요하다.